Mechanics and biology in intervertebral disc degeneration: a vicious circle. Issue 7 (July 2015) - Vergroesen, P.-P.A.; Kingma, I.; Emanuel, K.S.; Hoogendoorn, R.J.W.; Welting, T.J.; van Royen, B.J.; van Dieën, J.H.; Smit, T.H.
Summary: Intervertebral disc degeneration is a major cause of low back pain. Despite its long history and large socio-economical impact in western societies, the initiation and progress of disc degeneration is not well understood and a generic disease model is lacking. In literature, mechanics and biology have both been implicated as the predominant inductive cause; here we argue that they are interconnected and amplify each other. This view is supported by the growing awareness that cellular physiology is strongly affected by mechanical loading. We propose a vicious circle of mechanical overloading, catabolic cell response, and degeneration of the water-binding extracellular matrix. Rather than simplifying the disease, the model illustrates the complexity of disc degeneration, because all factors are interrelated. It may however solve some of the controversy in the field, because the vicious circle can be entered at any point, eventually leading to the same pathology. The proposed disease model explains the comparable efficacy of very different animal models of disc degeneration, but also helps to consider the consequences of therapeutic interventions, either at the cellular, material or mechanical level.